THE EFFECT OF SEASONS AND DEPTHS ON GROWTH AND SURVIVAL RATE OF PEARL OYSTER (Pinctada maxima) IN KODEK BAY, NORTH LOMBOK - M. S. Hamzah; Bisman Nababan (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
The pearl oyster (Pinctada maxima) farming in the West Nusa Tenggara waters in particular and in other areas, complained to the mass mortality of pearl oysters saplings on shell width between 3-4 cm. The mass mortality, allegedly as a result of changing in environmental conditions and triggered by the shift in seasons. This research aimed to determine the effect of seasonal variations in water conditions at different depth levels on growth and survival of seedlings of pearl oysters conducted on March 23, 2008 to February 22, 2009. This research was very useful for pearl oyster farming in an effort to suppress the mass mortality rates based on the appropriate level of depth and seasons. Analysis of variance showed that the seasonal factors, the level of depth, and the interaction between both factors responded very significantly on pearl oyster seedling survival. The "significant difference test" showed that the interaction between season and level of 2 m depth provided the best result with 100% survival. The similar survival rate was also found at a depth of 8 m during the transition season I and the east season. For single factor (depth), the best result for growth and survival rate was found in 2 m deep during the transition season I.Keywords: Oyster sapling, Pinctada maxima, growth, mortality, season, depth, Kodek Bay